Microbiota of Arctic mosquitoes - Kličić, Amila (Jihočeská univerzita, 2021)
The aims of this thesis are: 1. Describe the microbiome of the mosquito Aedes nigripes, a unique species inhabiting Arctic areas, in comparison with other mosquito species from temperate climates. 2. Evaluate the seasonal (i.e. different weather conditions) effect on Ae. nigripes microbiome. 3. Discuss the potential of Ae. nigripes to become a vector of viruses according to the possible vector-pathogen-microbiome interactions that could occur in the event of global warming.
Microbiota of Arctic mosquitoes
Keywords: MicrobiotA; Arctic; mosquito; climate change; Microbiota; Arctic; mosquito; climate change